New Research methods of Sales-Marketing Interfaces - Hetényi, Gábor (International Journal of Engineering and Management Sciences, 2020)
The energy invested in research in this topic is justified by the fact that the lack of optimal integration between SM (sales-marketing) can negatively affect overall corporate efficiency. The aim of this article is to present possible research methods that can reveal the impact of selected indicators, such as information exchange, coordination, vision and communication, conflicts, on the operation of the SM interface, according to Hungarian and foreign employees of international companies, and how they affect sales and marketing collaboration between pharmaceutical companies (PMC) and non-pharmaceutical companies (NPMC). It also attempts to demonstrate how the Partial Least Square (PLS) path modeling technique can provide valuable information on the consequences of management activity, and how the methods provided by Voyant Tools provide further research through quantitative analysis of qualitative data on the marketing sales interface (SMI), they can open up opportunities. The PLS-PM modeling technique was used to explore the relationships between the selected factors and possible hidden variables. These results clearly demonstrate that there are factors that influence SM collaboration that operate differently in PMCs and NPMCs, and that nationality differences can have a significant impact on how employees evaluate factors that affect SM collaboration. Of the methods we selected by Voyant Tools, the t-SNE (t-Distributed Stochastic Neighbour Embedding) tool proved to be the most sophisticated analysis, allowing the deepest analyzes by exploring relationships between groups of terms.